Weight Loss in Cancer and the 2017 Common Terminology Criteria for Adverse Events—Dangerous and Misleading - Aynur Aktas; Kunal C. Kadakia; Jake Waldman; Declan Walsh (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Accurate toxicity reporting in cancer clinical trials is necessary to promote regulatory decision making. Up to 85% of those with some cancers (e.g., oesophagus, head and neck, and pancreas) experience significant progressive weight loss (WL) throughout treatment. Therefore, it is necessary that investigators accurately grade and report WL. We have identified two dangerous and misleading approaches in the CTCAE specific to WL: (1) severity grades and associated clinical descriptions and (2) lack of pretreatment weight and longitudinal weight changes. This review highlights the critical importance of a more accurate, comprehensive and patient‐focused WL assessment in oncology clinical trials and the CTCAE. We offer a path forward for identification and management of this life‐threatening phenomenon, whether it is due to cancer or an antitumor treatment. The National Cancer Institute should consider the following five ideas and concrete action items for future CTCAE versions: (1) Weight assessment has important implications for toxicity determination and prognosis in clinical trials and should be consistently integrated into study reports; (2) Adverse event assessment should be patient‐focused and supported by clinically relevant definitions of each grade level; (3) the CTCAE grades and associated clinical descriptions for WL should be revised to better reflect the impact of WL on trial endpoints and patient safety; (4) WL should be assessed as a continuous variable to capture duration, severity, and trajectory; and (5) WL should be urgently incorporated into the PRO‐CTCAE to define the individual impact.